PRODUCT DIFFERENTIATION AND VALUE INNOVATION: REFRAMING COMPETITIVE STRATEGIES IN THE CREATIVE ECONOMY - Hery Margono (Ikatan Dosen Menulis, 2024)
The development of the creative economy has driven significant changes in competitive dynamics, where superiority is no longer solely determined by a product's physical attributes, but also by the experiences and perceptions formed in the minds of consumers. Increasingly intense competition and accelerating product change cycles require organizations to continuously deliver unique, relevant, and difficult-to-imitate features. Furthermore, the transformation in how value is created and delivered demonstrates that consumer engagement and experience consistency are increasingly crucial factors in building a competitive position. This study aims to examine how product differentiation and value innovation can be understood in an integrated manner to reshape competitive strategy within the context of the creative economy. This study uses a qualitative approach, utilizing various relevant literature sources for in-depth analysis. The results indicate that product differentiation and value innovation cannot be separated but must be strategically integrated to generate sustainable advantage. Furthermore, inter-functional coordination, flexibility in responding to change, and the ability to maintain value consistency are crucial factors in strengthening competitiveness. Furthermore, organizations that are able to manage complexity through an adaptive and integrated approach have a greater opportunity to maintain relevance and competitive position amidst the dynamics of the creative economy.